Image-based food volume estimation - Xu, C.; He, Y.; Parra, A.; Delp, E.; Khanna, N.; Boushey, Carol (Association for Computing Machinery, 2013)
In this paper, we propose an extension to our previous work on food portion size estimation using a single image and a multi-view volume estimation method. The single-view technique estimates food volume by using prior information (segmentation and food labels) generated from food identification methods we described earlier. For multi-view volume estimation, we use "Shape from Silhouettes" to estimate the food portion size. The experimental results of our volume estimation methods demonstrate our results with respect to accuracy and reliability. © Copyright 2013 ACM.